Pattern of use of medical information made available via an Internet website. - Dissanayake, V.H.W.; Jayasekara, R.W. (Sri Lanka Medical Association, 1999)
INTRODUCTION: The Internet is probably the fastest growing means of public communication. Those who seek health and medical information are using it increasingly. We decided to study the pattern of use of information made available via an Internet website. METHOD: Retrospective analysis of the entries made on the guest book and direct inquiries made to the webmaster of an established and well known Sri Lankan medical website from 1 February 1997 to 20 November 1998. RESULTS: During this period 23,373 web surfers visited the site. There were 222 guest book entries and 12 direct inquiries to the webmaster. The analysis of these entries and inquiries show that there is a wide gap in use of the information available at this website between web surfers from the developed and the developing countries. CONCLUSION: Governments in developing countries must plan to make computers and information technology as well as telecommunication services affordable and widely available.